PENGARUH PROBLEM BASED LEARNING DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Rozi Siregar; MHMD Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem-Based Learning (PBL) model and learning motivation on students' mathematics learning outcomes. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The subjects consisted of an experimental class implementing the PBL model and a control class using conventional learning. Data on mathematics learning outcomes were obtained through written tests, while data on learning motivation were collected through questionnaires. Data were analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and two-way ANOVA. The results showed that the Problem-Based Learning model significantly influenced students' mathematics learning outcomes. Furthermore, learning motivation also positively influenced mathematics learning outcomes. There was an interaction between the PBL model and learning motivation in improving students' mathematics learning outcomes. Therefore, the implementation of the Problem-Based Learning model is recommended to improve the quality of mathematics learning in schools.